THE IMPLEMENTATION OF GENRE-BASED APPROACH IN TEACHING WRITING TO THE EIGHTH YEAR STUDENTS OF SMP MUHAMMADIYAH 4 SURAKARTA - WIJAYANTI, DEWI RAGIL (2011)
This research aims to describe the implementation of Genre-based Approach in teaching writing by describing the objectives of Genre-based Approach (GBA) in teaching writing, the procedures of GBA in teaching writing, kinds of activities carried out of GBA in teaching writing, and the problems faced by teacher during the teaching-learning process. This research is a naturalistic research. In collecting the data the writer takes some methods, namely (a) interview, (b) document, and (c) observation. To analyze the data the writer takes some techniques, they are: (a) reducing the data, (b) displaying the data, and (c) drawing conclusion. In the result of this research shows that the objective of GBA in teaching writing helping the students to express their ideas in the form of written language and also enabling the students to understand written text and being active in practicing written form. This research also shows the procedures of GBA in teaching writing. The procedure used by teacher at SMP Muhammadiyah 4 Surakarta is appropriate with the theory of Genre. There are two patterns: BKOF, MOT, JCOT, ICOT and BKOF, MOT, ICOT. This research shows the kinds of activities of genre-based approach in teaching writing. In BKOF the activities are question and answer, and then giving explanation; giving the written text in MOT; the activity in JCOT is making a group and doing exercise from teacher; in ICOT the activities are doing task and classroom and doing task as homework. This research also shows the problems faced by teacher, they are: class management, different capability of the students, students low in vocabulary mastery. Based on the result, the conclusion of this research is the teacher implements the theory of genre. Although, the teacher takes the procedure of genre-based Approach, but teacher makes modification of it. Teacher doesn't use Joint Construction of Text (JCOT). The teacher focuses more on the Independent Construction of Text (ICOT).